A serovar analysis of heterosexual gonorrhoea in Edinburgh 1986-90. Issue 1 (February 1992) - Young, H; Moyes, A; Ross, J; McMillan, A
Abstract : OBJECTIVE–To analyse the frequency of different gonococcal serovars within Edinburgh, Scotland and to describe changes that occurred in the frequency of such serovars over time. METHODS–All heterosexual patients with a diagnosis of gonorrhoea confirmed on culture between January 1986 and December 1990 had their gonococcal strain serotyped. Temporal changes in the prevalence of gonorrhoea and the serovar of the isolates were analysed. RESULTS–Isolates of Neisseria gonorrhoeae from 1356 episodes of gonorrhoea were serotyped. Three serovars, Bajk (IB-3/IB-6), Bacejk (IB-1/IB-2) and Aedgkih (IA-1/IA-2), dominated, occurring in two-thirds of all infections. Over the study period Bajk (IB-3/IB-6) and Aedgkih (IA-1/IA-2) isolates declined in frequency in parallel with an overall fall in the prevalence of gonorrhoea but Bacejk (IB-1/IB-2) persisted at a lower but fairly constant level. Despite a fall in the number of gonococcal infections the variety of new serovars being isolated fluctuated. CONCLUSIONS–The ability of some serovars to persist while others decline in incidence may be partially related to antibiotic sensitivities but other factors such as an ability to evade the immune response and transfer of serovars from one population group to another may also be important.